Water dynamics at the nanoscale - Masciovecchio, C.; Bencivenga, F.; Gessini, A. (Condensed Matter Physics, 2008)
The recent construction of an Inelastic UltraViolet Scattering (IUVS) beamline at the ELETTRA Synchrotron Light Laboratory opens new possibilities for studying the density fluctuation spectrum, S(Q,E), of disordered systems in the mesoscopic momentum (Q) and energy (E) transfer region not accessible by other spectroscopic techniques. As an example of possible application of IUVS technique we will discuss the new insights provided in the case of water dynamics. From the analysis of IUVS spectra we were able to measure the temperature and pressure dependencies of structural relaxation time (τ) in water. In the case of room-pressure water the values of τ, as derived by IUVS, are fairly consistent with previous determinations and, most important, its temperature dependence agrees with Mode Coupling Theory (MCT) predictions. Moreover we found that τ decreases with increasing pressure at fixed temperature. The observed trend demonstrates that the structural relaxation phenomenology is strongly affected by the applied pressure. However, further investigations are necessary in order to clarify the physical meaning of these preliminary experimental results.